2020
DOI: 10.1002/ecy.2993
|View full text |Cite
|
Sign up to set email alerts
|

Trophic redundancy and predator size class structure drive differences in kelp forest ecosystem dynamics

Abstract: Ecosystems are changing at alarming rates because of climate change and a wide variety of other anthropogenic stressors. These stressors have the potential to cause phase shifts to less productive ecosystems. A major challenge for ecologists is to identify ecosystem attributes that enhance resilience and can buffer systems from shifts to less desirable alternative states. In this study, we used the Northern Channel Islands, California, as a model kelp forest ecosystem that had been perturbed from the loss of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 71 publications
2
41
0
Order By: Relevance
“…Likewise, southern California also has functional redundancy in urchin predators with California sheephead and spiny lobster Selden, Gaines, Hamilton, & Warner, 2017;Tegner & Levin, 1983), especially in several MPAs, which are included in our surveys there. Thus, the persistence of kelps in our southern California survey sites may reflect the protection of key sea urchin predators and an enhanced resistance and resilience of kelp forest communities to the loss of the sunflower star (Eisaguirre et al, 2020). These are only two examples of strong environmental and ecological differences among the ecoregions of the California Current large marine ecosystem.…”
Section: Geographic Range and Ecosystem Structure Shiftsmentioning
confidence: 93%
See 1 more Smart Citation
“…Likewise, southern California also has functional redundancy in urchin predators with California sheephead and spiny lobster Selden, Gaines, Hamilton, & Warner, 2017;Tegner & Levin, 1983), especially in several MPAs, which are included in our surveys there. Thus, the persistence of kelps in our southern California survey sites may reflect the protection of key sea urchin predators and an enhanced resistance and resilience of kelp forest communities to the loss of the sunflower star (Eisaguirre et al, 2020). These are only two examples of strong environmental and ecological differences among the ecoregions of the California Current large marine ecosystem.…”
Section: Geographic Range and Ecosystem Structure Shiftsmentioning
confidence: 93%
“…As a foundation species, changes in the abundance of kelp can have cascading effects on community structure and ecosystem function Byrnes et al, 2011;Carr & Reed, 2016;Edwards et al, 2020;Lamy et al, 2020;Miller et al, 2018;Schiel & Foster, 2015;VergĂ©s et al, 2016;Wernberg et al, 2012). In contrast, variability in community structure and species interactions may influence the resilience of kelps to projected warming (Eisaguirre et al, 2020;Ling et al, 2015). Building on global analyses of kelp dynamics (Krumhansl et al, 2016), a critical next step for understanding potential geographic variability in response to warming is to assess responses in the biological communities associated with these important foundation species.…”
Section: Introductionmentioning
confidence: 99%
“…In the Aleutian Archipelago, we have demonstrated that the trophic downgrading that has greatly eliminated foundational kelp species has also reduced variability in overall community structure and in the structure of trophic guilds. While functional redundancies among predators and herbivores can make diverse systems more stable 7 , 9 , simple food webs, such as those found in the Aleutian Archipelago, do not have the functional redundancies at higher trophic levels needed to maintain stability. Trophic rewilding (i.e., the restoration of apex predators) has been suggested for systems that have been downgraded 82 and may be one way that Aleutian kelp forests and their spatial variability can be restored.…”
Section: Discussionmentioning
confidence: 99%
“…Trophic downgrading occurs when apex predators have been extirpated over large geographic regions, which can lead to important consequences for ecosystem functioning due to both direct and indirect cascading effects 1 . This has been observed globally across a variety of terrestrial and marine ecosystems 2 – 7 . Often, trophic downgrading triggers increases in herbivore populations, thereby changing overall community structure 6 , 8 , 9 and altering patterns of ecosystem productivity 10 – 12 .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation